2017
DOI: 10.1016/j.avsg.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy in the Southern California Vascular Outcomes Improvement Collaborative

Abstract: Background The objective of this study was to examine the variation in practice patterns and associated outcomes for carotid endarterectomy (CEA) within the Southern California Vascular Outcomes Improvement Collaborative (So Cal VOICe), a regional quality group of the Vascular Quality Initiative. Methods All cases entered in the CEA registry by the So Cal VOICe were included in the study. Results From September 2010 through September 2015, 1,110 CEA cases were entered by 9 centers in the So Cal VOICe. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, protamine utilization has an extremely wide variation in practice patterns across hospitals, with some centers using none after CEA despite significant data demonstrating that protamine utilization is effective to lower bleeding complications. 2224 Given strong supporting data for using protamine to reduce bleeding after CEA, this could represent a target area for hospital-based quality improvement in terms of reducing readmission following CEA. Taking this a step further, there may be financial penalties for hospital systems that demonstrate hospital readmissions related to postoperative bleeding complications after CEA without protamine reversal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, protamine utilization has an extremely wide variation in practice patterns across hospitals, with some centers using none after CEA despite significant data demonstrating that protamine utilization is effective to lower bleeding complications. 2224 Given strong supporting data for using protamine to reduce bleeding after CEA, this could represent a target area for hospital-based quality improvement in terms of reducing readmission following CEA. Taking this a step further, there may be financial penalties for hospital systems that demonstrate hospital readmissions related to postoperative bleeding complications after CEA without protamine reversal.…”
Section: Discussionmentioning
confidence: 99%
“…4 Secondly, in our dataset we are unable to examine preoperative payment variation, however this was recently examined by Chan et al, where they found a wide variation in practice pattern and resource utilization in Southern California Vascular Outcomes Improvement Collaborative including increased preoperative cardiac stress testing and completion imaging suggesting our results are underestimating the total variation. 27 Additionally, our cohort examines only the Medicare population and does not include patients with Medicaid or private insurance, however in a recent study by Obeid et al, they found that 75.7% of asymptomatic and 73.9% of symptomatic patients were covered under Medicare. 28 This suggests that this dataset is likely to capture the majority of CEAs performed in the United States.…”
Section: Discussionmentioning
confidence: 99%